THE COMPANY'S STRATEGY TO REDUCE LOSSES DUE TO FOREIGN EXCHANGE RATES - Kaswoto, Junet; Sunaryo, Dede; Fitriana, Amalia Indah (Dynamic Management Journal, 2025)
Foreign exchange rate fluctuations can cause significant impacts for companies doing business internationally. Losses resulting from fluctuations in the exchange rate can cause uncertainty and lower the company's profits. Therefore, it is important for companies to adopt effective strategies in reducing foreign exchange rates. This study examines various strategies that can be used by companies to reduce losses due to foreign exchange rates. These strategies include static hedging such as the use of forward and options contracts, as well as dynamic hedging approaches that involve active management of hedged positions. In the context of PT. X in Banten Indonesia, the use of static hedging in the form of forward contracts can provide protection against exchange rate fluctuations associated with the company's international transactions. A dynamic hedging approach can also be an effective option for companies to optimize their protection against exchange rate risk. The results of the study show that the use of the hedging strategy implemented by PT. X in Banten can help companies reduce losses due to fluctuations in foreign exchange rates, especially dollars, and can improve the company's financial stability. The results of the analysis of forward hedging data conducted in certain periods show that there are (positive) gains in 2021 and 2022, and losses (negative) in the difference between the results of the forward hedging and the actual BI exchange rate at the time of maturity in 2023 in a few months.